APPLYING LITERARY ETHICAL CRITICISM TO TEACHING READING COMPREHENSION OF LITERARY TEXTS TOWARDS THE GOAL OF DEVELOPING STUDENTS' QUALITIES ACCORDING TO THE 2018 GENERAL EDUCATION PROGRAM - Do Thi Thuy Duong (Tạp chí Khoa học)
The article begins by applying moral literary criticism in teaching literary text comprehension and provides an overview of the theory of ethical literary criticism. It proposes an approach to literary texts from the perspective of moral literary criticism to develop students' qualities. The research is based on general research methods (theoretical and survey methods) and specific methods (structural analysis methods). The results show that applying moral literary criticism in understanding the texts of the Grade 12 Literature Textbook (Connecting Knowledge with Life series) is entirely feasible, paving the way for its implementation in other textbook series.